Interaksi Sosial dalam Kejadian Abortus Provokatus Kriminalis di Kabupaten Bulukumba Provinsi Sulawesi Selatan - Ridwan, Rizal; Prawitasari, Shinta; Prawirodihardjo, Leo (Fakultas Kedokteran, Kesehatan Masyarakat dan Keperawatan UGM, 2016)
Background: Many factors influence the decision to commit abortions, among all are marital status and educational status which most are still in school, economic pressure, multiparity or contaception failure. The social interaction is a connection between t the people who perform abortion and their suggestive environment.Objective: to observe the social interaction that happend among the person who perform abortion and the surrounding society.Method: This research makes use of qualitative method to understand the motives behind abortion practice, through an indepth interview. The sample collection is performed on H. A. Sulthan Dg Radja Hospital and Daffiku Hospital Bulukumba.Result and Discussion: Subject who performed abortion was influenced by internal and external factors. The internal factors include anxiousness, financial worrisome to support the child and fear of embarrassing the family in an unmaried women. As for the external factor includes pressure from families and friends who insist on performing abortion and the help from traditional healer on performing abortion. These two factors are not independent, and between them there are interactions to materialize abortion practice.Conclussion: Social interaction between individuals and between individual and the environment are an important role against abortion in decision making to have an provocative abortion.Keywords: Social interaction, abortion, factors for abortion